(untitled) (Third Sector Social Economic Review, 2026)
Women’s cooperatives stand out as important institutions supporting the economic, social, and psychological empowerment of women in societies experiencing poverty and gender inequality. Cooperatives offer women opportunities to generate income, participate in production, take part in decision-making processes, gain social visibility, and build solidarity networks. This study examines the subjective experiences of women participating in production in different women’s cooperatives and attempts to reveal, in a multidimensional way, how cooperatives contribute to women’s empowerment. The study was conducted using a phenomenological design, a qualitative research method. The study group consisted of 18 women who directly participate in production and generate income in women’s cooperatives operating in Antalya province, and participants were reached using the purposive sampling method. Data were collected through in-depth interviews and observations; the obtained data were presented by direct quotation using thematic analysis and descriptive analysis. Findings: Women’s reasons for joining cooperatives occurred in two ways. One was while seeking solutions to the difficulties they faced, and the other was to take advantage of opportunities that arose while they were engaged in production. The study determined that production processes in cooperatives are flexible, multifaceted, and hybrid in structure; and that income sharing is based on participation in production and labor intensity. It was found that the women included in the research experienced changes in their perspectives on life, self-confidence and belief in themselves, independence, knowledge, production methods, income, family and close circle relationships, social status, and participation in social life as a result of joining cooperatives.